Pengaruh Bimbingan Kelompok Dengan Teknik Reinforcement Positif Dan Self Management Untuk Meningkatkan Konsentrasi Belajar - Saputra, Yogie Wahyu Ari (Universitas Muhammadiyah Magelang, 2020)
This study aims to examine the group guidance on reinforcement positive and self management techniques on increasing student concentration. This research was carried out in class VIII SMP N 8 Magelang. This Study uses a pretest-posttest control group design. The sampel taken in this study was 16 students with the devision of 8 students as the experimental group one and 8 as the eksperimental group two. Sampling using cluster random sampling technique. Data collection in this study was carried out using a learning concentration. The data analysis method used is the One Way Anova parametric analysis. The results Showed that the group guidance on Reinforcement pisitive and Self Management techniques on increasing student concentration. This can be proven from the Anova test result in the experimental group with the probability value of Sig. 0,00<0,05 (2-Tailed). Based one the results of the analysis and discussion there is a difference in the score of the learning concentration scale between the exsperimental group one and the exksperimental group two which is 23,49 % higher than the eksperimental group two 14,01 %. The results of the study can be concluded that the group guidance of behavioral Reinforcement pisitive and Self Management techniques on increase student concentration.